Filosofi Organisasi dalam Konteks Manajemen Pendidikan: Studi di Sekolah Tinggi Ilmu Ekonomi "X" - Salfen Hasri (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2003)
A philosophy of an organization is the organization’s members’ way of thinking. The philosophy is part of the organization’s culture which is defined as how members give meaning to values, belief, customs, and philosophy of their organization as indicated by the members’ behavior which can differentiate that organization from others. The functions of the philosophy are to activate, to guide how to think, behave, and feel which influence the educational management practice.